Noninvasive vaccination against infectious diseases (2018)
The development of a successful vaccine, which should elicit a combination of humoral and cellular responses to control or prevent infections, is the first step in protecting against infectious diseases. A vaccine may protect against bacterial, fungal, parasitic, or viral infections in animal models, but to be effective in humans there are some issues that should be considered, such as the adjuvant, the route of vaccination, and the antigen-carrier system. While almost all licensed vaccines are injected such that inoculation is by far the most commonly used method, injection has several potential disadvantages, including pain, cross contamination, needlestick injury, under- or overdosing, and increased cost. It is also problematic for patients from rural areas of developing countries, who must travel to a hospital for vaccine administration. Noninvasive immunizations, including oral, intranasal, and transcutaneous administration of vaccines, can reduce or eliminate pain, reduce the cost of vaccinations, and increase their safety. Several preclinical and clinical studies as well as experience with licensed vaccines have demonstrated that noninvasive vaccine immunization activates cellular and humoral immunity, which protect against pathogen infections. Here we review the development of noninvasive immunization with vaccines based on live attenuated virus, recombinant adenovirus, inactivated virus, viral subunits, virus-like particles, DNA, RNA, and antigen expression in rice in preclinical and clinical studies. We predict that noninvasive vaccine administration will be more widely applied in the clinic in the near future. © 2018, © 2018 The Author(s). Published with license by Taylor and Francis. © 2018, © Zhichao Zheng, Diana Diaz-Arévalo, Hongbing Guan, and Mingtao Zeng.